Antimicrobial use in the Alberta sheep industry - Avery, Brent P. (Canadian Veterinary Medical Association, 2008)
Information regarding antimicrobial use in sheep is scarce. In 2001, a scrapie surveillance program was initiated in Alberta that also provided a mechanism for collecting other sheep health data including antimicrobial use information between April 2001 and April 2002. A major objective of this study was to describe antimicrobial use in the Alberta sheep industry. This was done by obtaining qualitative antimicrobial use information from all flocks (n = 212) providing cull ewes to the program using a brief, primarily flock-level, questionnaire. The respondents’ flocks represented 13.6% of the total provincial flock in Alberta in 2001. By a substantial amount, the most frequent method of administering antimicrobials was through injection followed by in-feed, oral (liquids, pills, boluses), and in-water routes, respectively. Drug-specific use data were collected for injectable antimicrobials only, with the most commonly used antimicrobial classes being penicillins followed by tetracyclines. Producers rarely treated some or all of their flock with injectable antimicrobials after discovering an individual sick animal. Adult sheep were the most common age group treated with injectable antimicrobials and the most frequent reason for injectable antimicrobial use was mastitis followed by respiratory problems. This study provides some initial insight regarding antimicrobial use in Alberta sheep flocks. However, collection of more drug-specific data (drug type, dose/concentration, duration of treatment) for noninjectable routes of administration should be conducted in future studies. Assessing antimicrobial use in other sectors of the Alberta sheep industry (feedlots) and other provinces across Canada would also be beneficial.